2015
DOI: 10.1123/jis.2014-0105
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Stressors in a Division II Historically Black University

Abstract: The purpose of this study was to further the research by studying coaches at a Historically Black College/University (HBCU) and Division II (DII) athletic program. Participants included seven head and five assistant coaches across seven sports. All coaches were interviewed, based on a preexisting interview guide (Olusoga et al., 2009). Data were content analyzed using previously agreed upon procedures and submitted in NVivo for further examination (Côté, Salmela, Baria, & Russell, 1993). Three higher order the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
(38 reference statements)
3
13
0
Order By: Relevance
“…During their interviews, the student-athletes admitted they had a challenging time balancing academic and athletic responsibility at HBCUs (Cooper & Hawkins, 2002). This research is consistent with later work by Robbins, Gilbert, and Clifton (2015), who found the lack of funding at HBCUs caused teams to travel by bus on long rides, typically across state lines. Furthermore, coaches at HBCUs typically have to monitor study hours on these long trips, adding responsibilities to their already long list of duties (Robbins et al, 2015).…”
Section: Attracting Coaches and Student-athletes To Hbcussupporting
confidence: 90%
See 2 more Smart Citations
“…During their interviews, the student-athletes admitted they had a challenging time balancing academic and athletic responsibility at HBCUs (Cooper & Hawkins, 2002). This research is consistent with later work by Robbins, Gilbert, and Clifton (2015), who found the lack of funding at HBCUs caused teams to travel by bus on long rides, typically across state lines. Furthermore, coaches at HBCUs typically have to monitor study hours on these long trips, adding responsibilities to their already long list of duties (Robbins et al, 2015).…”
Section: Attracting Coaches and Student-athletes To Hbcussupporting
confidence: 90%
“…This research is consistent with later work by Robbins, Gilbert, and Clifton (2015), who found the lack of funding at HBCUs caused teams to travel by bus on long rides, typically across state lines. Furthermore, coaches at HBCUs typically have to monitor study hours on these long trips, adding responsibilities to their already long list of duties (Robbins et al, 2015). The financial strain at HB-CUs is noticeable and can be an issue when trying to attract the best coaches and student-athletes.…”
Section: Attracting Coaches and Student-athletes To Hbcussupporting
confidence: 90%
See 1 more Smart Citation
“…African Sports Coaches Sports coaching can be an inherently stressful profession. This is because coaches are responsible for more than just coaching the sport (Robbins, Gilbert, & Clifton, 2015). For example, sports coaches contribute to wider societal agendas such as improving health, social inclusion, lifelong learning, and community regeneration, as well as facilitating athletes' personal and social development (Fletcher & Scott, 2010).…”
Section: Development and Initial Validation Of An Instrument To Assesmentioning
confidence: 99%
“…For example, a range of stressors have been reported by elite coaches in the United Kingdom that relate to athlete concerns, managing the competitive environment, pressure, expectations, coaching responsibilities of the athlete, organisational management, competition preparation, sacrificing personal time, and isolation (Didymus, 2017;Olusoga et al, 2009;Rhind, Fletcher, & Scott, 2013;Thelwell et al, 2008). Factors such as lack of enjoyment, physical hardship, wanting more free time, losing consistently, and interference with family life have also been reported as reasons why coaches may leave their profession (Frey, 2007;Robbins et al, 2015). In two studies of South African coaches, Surujlal and Nguyen (2009) and Kubayi, Coopoo, and Morris-Eyton (2017) indicated that inadequate facilities, inadequate salaries, lack of equipment, lack of support, poor refereeing decisions, unsociable working hours, and job insecurity were stressors experienced by these individuals.…”
Section: Development and Initial Validation Of An Instrument To Assesmentioning
confidence: 99%